Validasi Optimasi Kekasaran Permukaan dan Keausan Tepi Pahat Proses Bubut Menggunakan Metode Taguchi dengan Data Tunggal - Ervin Dwi Saputro; Martowibowo, Sigit Yoewono; Tabah, Gagan Ganjar (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
The Taguchi method uses signal-to-noise ratio (S/N) analysis to obtain optimal values and requires repeated data collection combined with control factors. However, in practice, the Taguchi method is still not in accordance with this concept, even though there are standard analysis options that do not require repeated data collection. In this study, a validation study of the Taguchi method was conducted for the case of a single data collection by comparing the optimization results obtained against standard analysis and validation experiment results. Determination of validity is carried out based on four comparison parameters, namely the combination of control factors, prediction of optimum value, deviation of optimum value prediction, and ranking of control factor influence. This research was conducted using a turning process case study. From this research, it is concluded that the Taguchi method for optimization of a single data collection is valid.